Sociolinguistic Variation : Critical Reflections. - Fought, Carmen (Oxford studies in sociolinguistics., 2004)
This volume contains previously unpublished articles by the most prominent sociolinguists working in the study of language variation today, which when taken together both highlight this new direction, as well as critique conventional wisdom in this growing and vital field of study. The book is divided into four sections: methodology; place (the role of context); adult speech; and attitudes and ideologies.